Study on extracting surface meltwater on the Amery Ice Shelf based on a novel water index - Zheng Zhou; Xingdong Wang; Xingdong Wang; Zehao Sun; Yanchuang Zhao (Frontiers in Marine Science)
BackgroundTraditional water indices often misclassify shadows as water, especially in polar regions. This study aims to improve water extraction accuracy by analyzing the spectral characteristics of water and shadows.MethodsA statistical analysis of the reflectance curves between red and green bands was conducted using Landsat 8 and Sentinel-2 imagery. Based on the steepness of decline in reflectance, a new water index, WI2023, was proposed. The index was validated using 10 Landsat 8 and 10 Sentinel-2 images from the Amery Ice Shelf.ResultsThe WI2023 index showed significantly improved discrimination between meltwater and shadows. Compared to NDWI and other indices, WI2023 achieved the highest accuracy when benchmarked against high-resolution Sentinel-2 data (extraction accuracy of 95.02%).ConclusionThe WI2023 index provides a robust approach for meltwater extraction in polar environments, particularly in low-latitude and low-altitude areas. It offers potential improvements in polar hydrological studies and remote sensing applications.